Asuhan keperawatan pada pasien Chronic Kidney Disease stage V di ruangan rawat penyakit dalam rumah sakit umum daerah Aceh - Barlian, Barlian; Ahyana, Ahyana; Kamal, Anda (PT WIM Solusi Prima, 2025)
Chronic Kidney Disease (CKD) or chronic kidney failure, is a condition in which the kidneys lose their ability to regulate fluid and electrolyte balance and perform essential metabolic processes. This case study aimed to provide nursing care for a patient with CKD stage V in the Aqsha 1 Ward. Assessment findings revealed that the patient’s symptoms included shortness of breath, nausea, vomiting, oliguria, and loss of appetite. Other clinical findings included lower extremity edema, fluctuating body temperature, weakness, weight loss, a urea level of 71 mg/dL, serum creatinine of 6.15 mg/dL, hemoglobin of 9.4 g/dL, and hematocrit of 28%. The nursing problems included ineffective renal perfusion, hypervolemia, impaired gas exchange, ineffective peripheral perfusion, hyperthermia, activity intolerance, and risk of nutritional deficit. Interventions provided to Mr. B during the 5-day treatment period included the recommendation of a low-sodium diet, advising the use of ice cubes to alleviate thirst, monitoring the patient’s intake and output, and encouraging deep-breathing relaxation exercises. The patient was positioned in a semi-Fowler's position to facilitate breathing, and the consumption of beetroot juice was recommended to increase hemoglobin levels. Leg elevation to 30 degrees was implemented to manage edema, and collaboration with the healthcare team for pharmacological therapy was conducted. Regular hemodialysis was administered, and the patient adhered to a 1700 kcal renal diet with fluid restrictions. Back massages were suggested to enhance comfort, and the patient was encouraged to rest in bed to conserve energy. Nursing evaluations indicated that one problem (hyperthermia) was resolved, while six problems were partially resolved due to the ongoing hemodialysis and comorbid conditions such as diabetes mellitus and hypertension. This case study aims to guide nursing care for CKD stage V patients, with recommendations focusing on fluid management to reduce fluid overload and enhance their quality of life. Chronic Kidney Disease atau gagal ginjal kronik adalah kondisi menurunnya fungsi dalam mengatur keseimbangan cairan dan elektrolit serta kehilangan daya dalam proses metabolisme. Studi kasus ini bertujuan untuk memberikan asuhan keperawatan yang diberikan pada pasien chronic kidney disease (CKD) stage V di Ruang Aqsha 1. Hasil pengkajian menunjukkan pasien mengalami sesak nafas, mual, muntah, oliguria, penurunan nafsu makan, edema pada ekstremitas bawah, suhu tubuh naik turun, lemas, penurunan berat badan, ureum 71 mg/dL, serum kreatinin 6,15 mg/dL, hemoglobin 9,4, hematokrit 28%. Masalah keperawatan yang didapat adalah perfusi renal tidak efektif, hipervolemia, gangguan pertukaran gas, perfusi perifer tidak efektif, hipertermia, intoleransi aktivitas dan resiko defisit nutrisi. Intervensi yang diberikan pada Tn. B selama 5 hari rawatan berupa menganjurkan diet rendah garam, manganjurkan untuk mengulum es batu, memonitor intake dan output pasien, relaksasi nafas dalam, mengatur posisi semifowler, menganjurkan konsumsi jus buah bit untuk meningkatkan kadar hemoglobin, elevasi kaki 300, memonitor intake dan output pasien dan melakukan kolaborasi pemberian terapi farmakologis, on HD regular, diet ginjal 1700 kkal serta pembatasan cairan, menjurkan pijat punggung dan mengajurkan tirah baring. Evaluasi keperawatan didapatkan bahwa satu masalah keperawatan teratasi yaitu hipertermi dan enam masalah keperawatan teratasi sebagian dikarenakan pasien sudah menjalani hemodialisa dan memiliki penyakit kormorbid seperti diabetes mellitus dan hipertensi. Diharapkan dengan adanya studi kasus ini dapat menjadi referensi dalam memberikan asuhan keperawatan pada pasien dengan Chronic Kidney Disease (CKD) stage V. Rekomendasi yang dapat dilakukan yaitu pentingnya manajemen cairan upaya menurunkan kelebihan volume cairan dan meningkatkan kualitas hidup pasien gagal ginjal kronik.